Assembly of Mg‐Mo‐Al‐Layered double hydroxides (LDHs) @ MoO42− and Its Synergistic Photocatalytic Degradation of Phenol in Wastewater. Issue 40 (25th October 2022) - Fu, Yuxiu; Pang, Yaming; Zheng, Yinan; Song, Xiaoli; Gao, Liguo
Abstract: Mg 2+ ‐Mo 6+ ‐Al 3+ ‐MoO4 2− ‐Layered double hydroxides (LDHs) materials were successfully prepared via a hydrothermal method by doping Mo 6+ in hydroxide laminates and inserting MoO4 2− to replace the interlayer anions of LDHs materials. The samples were characterized by X‐ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscope (TEM), Fourier transform infrared spectrometer (FTIRS) and ultraviolet‐visible spectrophotometer (UV). The electronic density of states was calculated using the density functional theory (DFT) of Vienna Ab‐initio Simulation Package (VASP). The effects of Mo 6+ and MoO4 2− on the structure, morphology, electronic structure and photocatalytic performance of Mg 2+ ‐Al 3+ ‐LDHs were systematically studied. The conditions for phenol degradation by Mg 2+ ‐Mo 6+ ‐Al 3+ ‐MoO4 2− ‐LDHs were optimized by single factor analysis and response surface methodology. The results show that the MoO4 2− anion reduces the band gap width and thus enhances the absorption of low‐energy photons. The interaction between cations and anions enhances the photocatalytic performance. When the dosage of Mg 2+ ‐Mo 6+ ‐Al 3+ ‐MoO4 2− ‐LDHs was 0.03 g, the temperature was 40 °C and the visible light irradiation was 15 min, the removal rate of phenol reached 94.76 %. Abstract : Photocatalysts enhance the ability to absorb low‐energy photons due to the reduction of the band gap. Through the photocatalytic mechanism, it is known that when there is irradiation with light (hv) energy entering Mg 2+ ‐Mo 6+ ‐Al 3+ ‐MoO4 2− ‐Layered double hydroxides (LDHs), highly active hole‐electron pairs will be generated, and a large amount of ⋅OH will be generated after the reaction, which can completely oxidize the phenol in water into CO2 and H2 O.